Investigating the relationship between transformational leadership and Job satisfaction: An application on trainers - ALPULLU, AYTEKİN (My University, 2022)
Aim: This study aims to examine the relation between trainers’ job satisfaction serving in Youth and Sports Provincial and County Directorates and transformational leadership behaviors they perceive of their managers. Material and Method: In the study, quantitative method, correlational survey model was used, participants were determined by the convenience sampling method and a questionnaire was applied to 381 trainers. In data analyses; percentage (%), frequency (f), normality of data and Pearson correlation were applied. Significance level as p<0.05 and confidence interval were accepted as 95%. Results: The relationship between all dimensions of transformational leadership and job satisfaction was observed. Job satisfaction levels were also increased with rising perceptions of employees regarding transformational leadership. (r= 0.569; p<0.001). Positive relationship between the transformational leadership dimensions and the intrinsic dimension of job satisfaction from (r=0.412) to (r=0.447), and between the extrinsic dimension from (r=0.446) to (r=0.554) were found. Among values, the first highest value was between the dimension of individual attention relation and extrinsic job satisfaction (r=0.554), the second highest value was the between the dimension of individualized consideration and extrinsic job satisfaction (r= 0.523). Conclusion: Trainers' point of view on transformational leadership has shown that the relationship between extrinsic job satisfaction and transformational leadership dimensions is usually stronger than intrinsic job satisfaction. In terms of the job satisfaction of trainers, leadership is not the determining factor alone when it comes to job-related environmental factors. In this study, it has been determined that transformational leadership is related to job satisfaction and when there is an expansion in the perception levels of trainers as to transformational leadership, their job satisfaction levels have also expanded.

Amaç: Bu çalışmada Gençlik ve Spor İl ve İlçe Müdürlüklerinde görev yapan antrenörlerin iş tatmini ile yöneticileri için algıladıkları dönüşümcü liderlik davranışları arasındaki ilişkinin incelenmesi amaçlanmıştır. Materyal ve Metot: Çalışmada nicel yöntem, ilişkisel tarama modeli kullanılmış, katılımcılar kolayda örnekleme yöntemi ile belirlenmiş 381 antrenöre anket uygulanmıştır. Veri çözümlemelerinde; yüzde (%), frekans (f), verilerin normalliği, tanımlayıcı istatistikler ve Pearson korelasyonu uygulanmış, anlam düzeyi p<0,05 ve güven aralığı %95 kabul edilmiştir. Bulgular: Dönüşümcü liderliğin tüm boyutları ile iş tatmini arasında ilişki olduğu ve çalışanların dönüşümcü liderlik ile ilgili algılarında artış söz konusu olduğunda iş tatmini düzeylerinin de arttığı gözlenmiştir (r=0,569; p<0,001). Dönüşümcü liderlik alt boyutları ile iş tatmininin içsel alt boyutu arasında (r=0,412) den (r=0,447) ye ve dışsal alt boyutu arasında (r=0,446) dan (r=0,554) e kadar pozitif yönlü ilişki olduğu bulunmuştur. Bu değerler arasında en yüksek değer olarak bireysel ilgi boyutu ile dışsal iş tatmini (r=0,554), ikinci en yüksek değer ise idealleştirilmiş etki (atfedilen) boyutu ile dışsal iş tatmini (r= 0,523) arasında olduğu tespit edilmiştir. Sonuç: Antrenörlerin dönüşümcü liderliğe bakış açısı, dışsal iş tatmini ile dönüşümcü liderlik boyutları arasındaki ilişkinin genellikle içsel iş tatmininden daha güçlü olduğunu göstermiştir. Antrenörlerin iş tatmini açısından iş ile ilgili çevresel faktörler söz konusu olduğunda liderlik tek başına belirleyici faktör değildir. Bu çalışma, dönüşümcü liderliğin iş tatmini ile ilişkili olduğunu ve antrenörlerin dönüşümcü liderlik ile ilgili algı düzeylerinde artış söz konusu olduğunda iş tatmini düzeylerinin de arttığı belirlenmiştir.
Dönüşümcü liderlik ile iş tatmini ilişkisinin incelenmesi: antrenörlere yönelik bir uygulama
Keywords: Transformational Leader; Job Contentment; Coach; Sport; Dönüşümcü Lider; İş Doyumu; Antrenör; Spor